Factors Related to WUS' Interest in IVA Examination at Helvetia Health Center in 2022 - Pemiliana, Putri Diah; Maysarah, Dede; Sari, Niken Novita (Pena Cendekia Insani, 2023)
Introduction: Cervical/cervical cancer is a malignant tumor that grows in the cervix/cervix. According to the World Health Organization (WHO), cervical cancer is the fourth most common cancer in women with 570,000 new cases in 2018 representing 6.6% of all female cancers. Based on the initial survey data that the researchers conducted in October 2022, there were 3 people who were interested in having an IVA examination, and 12 people who were not interested in having an IVA examination. Purpose: The aim of this study was to determine factors related to WUS interest in IVA Examination at the Helvetia Public Health Center in 2022. Methods: This study used an analytic survey design with a cross-sectional approach. The population of this study were all married WUS in the working area of the Helvetia Health Center in 2022 with a total of 4,746 people. The sample of this research is 98 people. The sampling technique is Simple Random Sampling. Methods of data analysis by means of univariate and bivariate analysis with chi-square test. Results: Based on the results of the study of 98 WUS, it was shown that there was a relationship between attitude and interest in carrying out IVA examinations with a p-value = 0.023, there was a relationship between husband's support and an interest in carrying out IVA examinations with a p-value = 0.009, and there was a relationship between distance from health facilities and interest perform an IVA examination with a p-value = 0.017. Conclusion: The conclusion in this study is that there is a relationship between attitude, husband's support, and distance to health facilities with an interest in conducting VIA examinations at the Helvetia Health Center in 2019. It is recommended for health workers to conduct cervical cancer counseling and invite WUS who have had sexual intercourse for detection early cervical cancer by doing IVA.